(untitled) (Development Service Industry Management, 2025)
The Sustainable Development Goals (SDGs) provide a comprehensive framework to address many global challenges through collaborative efforts across economic sectors. The hotel business takes responsibility for the implementation of the SDGs and actively integrates them into its core strategies and activities. Successful achievement of the SDGs by hotel companies will enable them to minimise the negative impact on the environment by enhancing synergies between the SDGs, which will provide unique opportunities to achieve multiple SDGs simultaneously and ensure competitive advantages in the hospitality industry. The purpose of this article is to substantiate and summarise the synergies and trade-offs between the SDGs in the hotel industry as an indicator of business sustainability. The article summarises the SDGs by three components: environmental, social and economic. It substantiates the extent to which the SDGs influence each other, creating a certain interaction that allows to establish a certain correlation between them. A significant positive correlation between several SDG indicators is classified as synergy, while a significant negative correlation is classified as a trade-off. The study has identified synergies between the SDGs in the hotel industry, namely: SDG 6, SDG 7, SDG 11, SDG 14, SDG 15 and trade-offs with SDG 8, SDG 9 and SDG 12. It has been determined that it is almost impossible to achieve the SDGs through only one SDG, which requires simultaneous positive interaction between several SDG indicators. The article also summarises the trade-offs that arise between the SDGs in the hotel industry which may lead to the blocking of the achievement of one SDG due to the need to choose one of the goals to the detriment of another. The article analyses specific contradictions in the achievement of the SDGs that may be violated by the current policies of hotel companies and mitigates the relevant trade-offs. In addition, the article graphically presents a three-component model of sustainable development of the hotel business and provides data on the achievement of the SDGs by global hotel chains represented in Ukraine.